The Anatomy of Right Conus Artery and its Clinical Significance - Vijaya Kumar J2, Saraswathi P3, Udaya Sankari T1*, (Recent Research in Science and Technology, 2011)
Background of the study: An intimate knowledge of the anatomy of coronary arteries, the ‘Crown’ of the heart, does a self-evident pre-requisite for a complete understand of the coronary artery disease or for more intelligent planning of surgery. The right conus artery (R.Con.A) is the first ventricular branch of the right coronary artery (RCA). The aim of this study is to analyse the number and level of ostia in the anterior aortic sinus with regard to the sinu-tubular junction, pattern of origin of right conus artery, angulations of right conus artery, and the branching pattern of right conus artery. The above findings would be of great significance in the interpretation of coronary arteriography, angiography, surgical revascularization of myocardium and embryological interpretations. Methods: A total number of thirty cadaveric hearts and twenty angiograms were utilized for this study. This is carried out by dissection method and by coronary angiographic images study. The study is carried out to analyse the number and level of ostia in the anterior aortic sinus with regard to the sinu-tubular junction, pattern of origin of right conus artery, angulations of right conus artery, and the branching pattern of right conus artery. Results: The results shows that the percentage calculation of multiple ostium is less than double and single ostia. Individual having triple or multiple opening go in for cardiac problems. The percentage level of ostia, above the sinu-tubular junction was less than that of the below and at the level of sintubular junction. For the pattern of origin more population had the right conus artery arising from the right coronary artery. In this study the angulation between direct origin of right conus artery from aorta and the angulation between right coronary artery (RCA) and right conus artery was significant .The angulation study suggests that the right conus artery with aortic origin was obtuse and with right coronary artery it was acute. Regarding branches more population had long branches which were boon for them. The results of angiographic images regarding pattern of origin was almost nearer with the previous study and dissection method. The positive results found in the present study provide an extensive knowledge of the right conus artery pattern which is essential for the diagnostic and therapeutic interventional procedures. Conclusion: The existence of right conus artery bridges for collateral circulation between the right and left coronary system which is really significant in ischaemic changes of heart.